Electromechanical transmission of tracked machine energy characteristics study - V. N. Kuznetsova; R. V. Romanenko (Вестник СибАДИ, 2021)
Introduction. The use of an electromechanical transmission in the design of a tracked vehicle allows an increase in the complex indicator of mobility, an increase in the range, fuel efficiency, maximum speed, a decrease in acceleration time, etc. The improvement of these indicators is achieved mainly due to the different performance characteristics of the internal combustion engine and the energy characteristics of electrical machines. The latter fact makes it possible to ensure the operation of the power plant of the tracked vehicle in such a way as to avoid unfavorable operating modes of both the internal combustion engine and the elements of the electromechanical transmission (a generator, a traction electric motor, an energy storage) from the point of view of energy efficiency, and to realize the high efficiency of the entire system.Research methods. To improve the mobility and implement a rational strategy for electromechanical transmission control, it is necessary to have an idea of the effective modes of operation of the main elements of the power plant. As a way to solve this problem it is proposed to study the energy characteristics of the main elements of an electromechanical transmission using the developed mathematical model for various modes of movement of a tracked vehicle.Results. Modeling the motion of a tracked vehicle with an electromechanical transmission makes it possible, in addition to determining the transmission parameters, to formulate preliminary requirements for its characteristics.Discussion and conclusion. To solve these problems, it is necessary to simulate the process of movement of a tracked vehicle, taking into account the initial data that are adequate to real operating conditions.